Analysis of the Dynamics of the Bovine Sector in Colombia and its Determinants from an ARDL Model - Diaz, Roberto Adolfo Diaz; Gonzalez, Consuelo Arce; Calderon, Jose Alejandro Vera (Journal of Ecohumanism, 2024)
The article carries out a comprehensive analysis of the beef production sector in Colombia using historical data and a time series model called Autoregressive Distributed Lags (ARDL). This approach allows estimating the relationships and significance of various explanatory variables of production in the sector. The results of the model reveal that beef production in Colombia is highly sensitive to domestic production and the domestic price, while exports, the international price and the exchange rate (TRM) do not show considerable statistical significance. This analysis provides a detailed understanding of the factors influencing beef production in Colombia, highlighting the importance of the domestic market over external influences .